Mineralización de la paja de caña de azúcar en suelo adicionado con viñaza (suproducto de la industria del alcohol de caña de azúcar) y fertilizante nitrogenado - Sanomiya, Luciana Terumi [UNESP]; Assis, Luis Carlos [UNESP]; Oliveira, João Ademir de [UNESP]; Nahas, Ely [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2006)
Cellulose is the most abundant vegetable organic compound, being derived mainly from plant residues. The decomposition of sugar-cane (Saccharum officinarum L.) straw was studied in a period up to 90 days, through variables related to the carbon cycle, such as respiratory activity and CM-cellulase (CM, cellulose microcrystalline) and CMC-cellulase (CMC, carboxymethylcellulose) activities. The treatments consisted of 0, 0.5 and 1.0% of straw, in the presence and absence of vinasse (a sugar-cane alcohol industry byproduct) and nitrogen fertilizer. The respiratory and cellulase activities increased up to the 14th day of incubation and later decreased. The respiratory activity was 1.9 and 2.3 fold larger (P < 0.05) in the soil with 0.5 and 1.0% of straw added, respectively, in relation to the control. CM- and CMC- cellulase activities also increased from 1.8 to 2.9 and from 2.3 to 2.7 fold, respectively. The vinasse addition enhanced CO 2 production and CM-cellulase activity, however, no significant effect was observed on CMC-cellulase activity. The addition of N reduced both respiratory and cellulase activities. The decomposition of the sugar-cane straw may enhance soil nutrient cycling increasing agricultural production. © 2006 Instituto de Investigaciones Agropecuarias, INIA.
Mineralization of sugar-cane straw in soil amended with vinasse (a sugar-cane alcohol industry byproduct) and nitrogen fertilizer
Keywords: CM-cellulase; CMC-cellulase; Mineralization; Respiratory activity; Sugar-cane straw; Saccharum; Saccharum hybrid cultivar; Saccharum officinarum